DEVELOPMENT AND EVALUATION OF RICE BRAN ENRICHED READY TO COOK EXTRUDATES - B. NEERAJA PRABHAKAR and B. ANILA KUMARI, N. BHAGYA LAKSHMI, JESSIE SUNEETHA, W, K. UMA MAHESWARI (The Journal of Research, PJTSAU, 2019)
In this era of global industrialization and advancement of technologies, the demand for ready to eat foods like extruded foods has increased and these are rich in starch, fat and energy but depleted in fiber leading to gastrointestinal and cardiovascular diseases (Grewal, 2007). The food processing industry produces large quantities of waste products (Chauhan and Intelli, 2015).